2011
DOI: 10.1111/j.1365-2648.2011.05619.x
|View full text |Cite
|
Sign up to set email alerts
|

Keeping patients safe in healthcare organizations: a structuration theory of safety culture

Abstract: Applying structuration theory to the concept of safety culture reveals a dynamic system of individual action and organizational structure constraining and enabling safety practice. Nurses are central to the (re)production of this safety culture system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 22 publications
2
65
0
2
Order By: Relevance
“…Therefore, the impact of the factors that favor patient safety is expected to be felt in the future, and the findings of this study may contribute to change the focus of the institution to the search for a safety culture (8) . The low scores of the domain perception of hospital and unit management suggest that the institution should focus on leadership skills training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the impact of the factors that favor patient safety is expected to be felt in the future, and the findings of this study may contribute to change the focus of the institution to the search for a safety culture (8) . The low scores of the domain perception of hospital and unit management suggest that the institution should focus on leadership skills training.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the environment of health organizations is a determining factor in the quality and safety of health care, and the nursing team provides a significant contribution to the creation of a safety environment for health. The major role played by the nursing team in this regard can also be explained by the fact that this team adds knowledge on the health environment due to the proximity of nurses to patients (8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional staff nurses are most likely involved in adverse events and an estimated 11 million nurses throughout the world have a critical impact on safety initiatives [9]. Several studies have indicated that long working hours have adverse effects on nurse performance.…”
Section: Introductionmentioning
confidence: 99%
“…From a benevolent orientation, the mitigation of adverse health events is optimized through vigilance and commitment to evidence informed practice. Patient safety is recognized as a transglobal mandate central to nursing care across all sectors and settings [3,4]. Beyond a mandate, the Canadian Nurses Association characterizes the commitment to patient safety as an ethical obligation.…”
Section: Introductionmentioning
confidence: 99%